Strategic Agility and Performance of Small and Medium Enterprises in the Phase of Covid-19 Pandemic - Emejulu Gerald; Agbasi Obianuju; Nosike Chukwunonso (Goodwood Publishing, 2020)
Purpose: This study examined the impact of strategic foresight (SF) on the competitive advantage (CA) of SMEs in Anambra State. Research methodology: Survey research design was chosen for the work. The population was 1500, while the sample size was 306 business owners arrived at using Krejcie and Morgan formula. Split-Half technique was used in testing the reliability of the self-structured questionnaire, and the result obtained was .891. Data were analysed using Simple Regression Technique, and the hypothesis was tested at 5% level of significance. Results: The findings revealed that SF has a relationship with CA (r = .968) while coefficient of determination (R2) indicates that a 92% change in CA is accounted for by changes in SF (R2 = .938; F = 4070.780, p-value < 0.05). Conclusion: This study concludes that strategic foresight (SF) significantly enhances the competitive advantage (CA) of SMEs in Anambra State. A higher level of SF leads to a greater improvement in CA, helping businesses anticipate trends and stay competitive. Future research could expand to other regions to confirm these findings. Limitations: This study is limited by scope as only SMEs in Anambra State were studied which may not be enough to make an inference. Contributions: This study will help small and medium-sized enterprises to realize the importance of keeping them aware not only of what is happening in their business environment, but also outside of their immediate environment.